Comparison of analgesic efficacy between intrafunicular and intratesticular lidocaine injection in dogs - Lohinger, Christian; Verdier, Natali; Klonner, Moriz Ettore; Braun, Christina; Auer, Ulrike (Frontiers in Veterinary Science, 2026)
Elective surgical orchiectomy is a commonly performed procedure in dogs that requires adequate pain management. Multiple studies have shown that various local anaesthetic techniques improve analgesia and may reduce side effects associated with systemically administered drugs. This study aimed to compare the analgesic efficacy of an injection and an ultrasound-guided intrafunicular injection of lidocaine. In total, 28 dogs were included in this study: 13 dogs received an intratesticular injection, whereas 15 dogs received an ultrasound-guided intrafunicular injection. Assessed data included the time needed to perform the locoregional technique, time between locoregional anaesthesia and skin incision, removal of the second testicle, and end of surgery; intraoperative vital parameters, quality of recovery, postoperative pain scores, and serum cortisol levels. The time to perform the ultrasound-guided intrafunicular block (96.13 ± 30.67 s) was significantly longer than the intratesticular block (23.20 ± 5.57 s). Both techniques proved to be feasible and effective with a similar success rate.